Association between Laryngeal Airway Aperture and the Discharge Rates of Genioglossus Motor Units - LaCross, Amy; Watson, Peter J.; Bailey, E. Fiona (Frontiers in Physiology, 2017)
We know very little about how muscles and motor units in one region of the upper airway are impacted by adjustments in an adjacent airway region. In this case, the focus is on regulation of the expiratory airstream by the larynx and how changes in laryngeal aperture impact muscle motor unit activities downstream in the pharynx. We selected sound production as a framework for study as it requires i) sustained expiratory airflow, ii) laryngeal airway regulation for production of whisper and voice and iii) pharyngeal airway regulation for production of different vowel sounds. We used these features as the means of manipulating expiratory airflow, pharyngeal and laryngeal airway opening to compare the effect of each on the activation of genioglossus (GG) muscle motor units in the pharynx. We show that some GG muscle motor units a) discharge stably on expiration associated with production of vowel sounds, b) are exquisitely sensitive to subtle alterations in laryngeal airflow and c) discharge at higher firing rates in high flow vs. low flow conditions even when producing the same vowel sound. Our results reveal subtle changes in GG motor unit discharge rates that correlate with changes imposed at the larynx, and which may contribute to the regulation of the expiratory airstream.